PERILAKU AFEKTIIF PERILAKU AFEKTIIF: PERILAKU AFEKTIIF - Alun Matiti; Frezy Paputungan (Jurnal Ilmu Pendidikan dan Budaya, 2022)
This article discusses affective behavior, which is itself a natural thing and an integral part of human experience. The emotions and feelings we feel play an important role in shaping our response to the environment and also affect our quality of life. This article is presented using qualitative methods. Affective behavior is an important aspect of human life that involves a person's emotional reactions, feelings, and moods. The term "affective" refers to how individuals feel and express their emotions towards certain situations or stimuli. Affective behavior includes various aspects such as joy, sadness, anger, fear, and various other feelings that can affect the way we interact with the world around us. The factors above interact and influence each other in shaping a person's affective behavior. Emotions influence various aspects of daily life and play a role in decision making, social interaction, mental well-being, and the quality of interpersonal relationships. Affective behavior involves a person's emotional reactions, feelings, and moods to certain situations or stimuli. These behaviors play an important role in human life and affect how we interact with the world around us. Factors that influence affective behavior include receiving or paying attention, responding, appreciating, organizing values, and character. Emotions play an important role in affective behavior, including decision making, communication and social interaction, motivation and satisfaction, emotion regulation, and interpersonal relationships. It is important to understand and manage emotions well in order to improve quality of life and build healthy relationships. Strategies that can be used to manage and understand emotions include controlling emotions, choosing the right emotion according to the situation, and developing emotion regulation skills.